2017
DOI: 10.6007/ijarbss/v7-i6/2959
|View full text |Cite
|
Sign up to set email alerts
|

The Confirmatory Factor Analysis (CFA) of Preschool Management Model in Sarawak

Abstract: In several years, structural equation modeling or popularly known as SEM is the first generation path modeling widely used by researchers and practitioners nowadays to analyze the interrelationship among variables in a model. In this study, the questionnaire was designed based on six constructs which is headmaster's instructional leadership as exogenous and parental involvement in preschool education, preschool teachers' information and communication technology (ICT) in teaching, teacher professional developme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 10 publications
1
4
0
Order By: Relevance
“…This study revealed that the Effect Expectancy (EE) has significantly influence the user's Trust (TR) when using the Facebook in their daily life. It was supported by previous study by Shau (2017) that found the user's trust influenced by EE. Besides, the results of effort expectancy do not significantly influence user's continuance intention in using Facebook.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…This study revealed that the Effect Expectancy (EE) has significantly influence the user's Trust (TR) when using the Facebook in their daily life. It was supported by previous study by Shau (2017) that found the user's trust influenced by EE. Besides, the results of effort expectancy do not significantly influence user's continuance intention in using Facebook.…”
Section: Discussionsupporting
confidence: 76%
“…Moreover, the measure of correlation between exogenous constructs (effort expectancy, social influence and privacy concerns) are 0.09 (between effort expectancy and social influence), 0.12 (between social influence and privacy concerns) and 0.39 (between effort expectancy and privacy concerns). All the correlation between exogenous constructs is below 0.85 indicates that discriminant validity is achieved and not redundant with each other's (Shau, 2017). The result of regression weights for each path in this study were presented in Table 9.…”
Section: The Structural Modelmentioning
confidence: 87%
“…Composite reliability results of all the variables show a value above the .6 thresholds indicating the composite reliability. The last element examined is the AVE and has a threshold of 0.5 as per Shau (2017). Therefore, all the constructs have a value of AVE above 0.5, which meets the point.…”
Section: Measurement Modelmentioning
confidence: 84%
“…Moreover, (Garson, 2012) determined that the measurement of the factor loading provides the variance extracted by the factor from the variable. According to (Shau, 2017), the threshold for factor loadings is 0.6, and the items must possess factor loading above 0.6 to ensure eligibility. Therefore, it can be determined based on the below Table 1 that the minimum value for factor loading is 0.755, which is well above the threshold of 0.6.…”
Section: Confirmatory Factor Analysismentioning
confidence: 99%